GENDER-BASED DEVELOPMENT AND IMPLEMENTATION OF E-LEARNING IN ISLAMIC HIGHER EDUCATION - Deasy Yunita Siregar; Ishaq Ishaq; Syahrial Arif Hutagalung (Journal of Gender and Social Inclusion in Muslim Societies, 2022)
The integration of e-learning in higher education encounters intricate problems, including the gender-based digital divide, which may impact equitable access to education. This study seeks to examine the evolution and execution of e-learning through a gender lens within the Department of Political Science at the Faculty of Sharia and Law, UIN Sumatera Utara. Data were obtained utilizing a descriptive qualitative methodology through observation, in-depth interviews with 10% of students (randomly selected to ensure balanced gender representation) and instructors, as well as document analysis and literature reviews. The data analysis utilized qualitative methods incorporating a gender analysis framework. The research findings reveal: (1) merely 30% of lecturers utilize e-learning; (2) a gender disparity exists in technological access, with female students experiencing restricted access to personal devices; (3) digital literacy varies by gender owing to unequal socialization and opportunities; (4) participation trends indicate that female students prefer textual contributions over oral communication; (5) the dual burden of domestic responsibilities impedes the full participation of female students and lecturers. Obstacles encompass the digital access divide, disparities in digital literacy, gender norms, socio-cultural conventions, and insufficient gender-sensitive training. This study advocates for the formulation of gender-responsive e-learning policies, the enhancement of equitable technology access, the provision of inclusive digital literacy training, the creation of gender-neutral material, and the establishment of a gender-based monitoring system to guarantee equality in Islamic higher education.